Determinants of infant mortality in rural India: An ecological study - Abhijit Mukherjee; Sharmistha Bhattacherjee; Samir Dasgupta (Wolters Kluwer Medknow Publications, 2019)
Background: Long-term reductions in infant mortality (IM) are possible only by addressing the distal determinants. Objectives: The objective of the present study was to determine the relationship between IM and its major distal determinants in rural India. Methods: The dependent variable used in the study was state wise IM rate (IMR), the values of which were obtained from the Sample Registration System, 2015. State level literacy rate in females, unemployment rates of females, GINI index, and round-the-clock neonatal services in primary health centers in the rural areas and the per capita gross state domestic product at purchasing power parity (GSDP at PPP) of the states, were used as the predictor variables for IM. Relationship between the variables was obtained by the Pearson's correlation coefficient. Bivariate and multivariable linear regressions were used to identify the magnitude and direction of the predictors on IM. Results: Correlation statistics showed none or weak positive correlation between the Gini coefficient and 24 × 7 primary health-care services and IMR. There was a strong negative correlation between female literacy rate and IMR, while the unemployment rates and per capita gross state domestic product (GSDP) were moderately negatively correlated to IMR. Bivariate analysis revealed that, for unit increase in unemployment rates in females, proportion of literate women, and 1000$ increase in the GSDP at current prices, IMR decreased by 0.07, 0.763, and 1.702, respectively. However, after adjustment, only the female literacy rates showed significant association with IMR. Conclusions: Of the major determinants included in the study, rural female literacy is the most important distal determinant of IM in rural areas of India.